A Study on the Steady and Dynamic Performance of Dry Gas Seals with Combined Superelliptical Grooves and Holes on the End Face - Li, Yushi; Chen, Yuan; Li, Yuntang; Li, Xiaolu; Wang, Bingqing; Jin, Jie (Recent Patents on Mechanical Engineering, 2024)
Background: Enhancing the stability and leakage control of Dry Gas Seals (DGS) under high parameters has been a crucial research focus. The design of end-face groove structures and surface texture shapes has been an essential aspect of DGS studies aimed at improving performance. Objective: The proposed end-face gas seal utilizes superelliptical grooves and holes to improve its performance, aiming to obtain a patent. The use of superelliptical curves allows for a more precise and efficient geometric representation, resulting in a better sealing effect. Methods: A theoretical analysis model for the steady and dynamic behavior of the seal is established using the lubrication theory and perturbation methods. The study investigates the distribution patterns of gas film pressure on the sealing end-face and gas flow characteristics within the film. This approach provides a new perspective for understanding seal performance and offers a theoretical basis for optimizing seal design. Results: The results indicate that the combined end-face structure with grooves and holes ensures good sealing stability and effectively enhances leakage control performance. By optimizing the design of the superelliptical groove and holes on the end face, the performance of DGS can be significantly improved. Conclusion: Within the parameter range studied, better steady-state performance is achieved for θ=40 80°, v=1.3 1.4, u=1 2, β=0.6 0.7, and λ=1.0 1.5. In addition, better dynamic performance is observed for θ=80 120°, v=1.1 1.2, u=2 3, β=0.9 1.0, and λ=2.0 2.5.
Keywords: finite difference method